Brazil : Financial Sector Assessment Program-Technical Note on Fund Management: Regulation, Supervision and Systemic Risk Monitoring. (IMF Staff Country Reports; Country Report ;, 2018)
Brazil has a large and diverse investments funds sector which is subject to a robust regulatory framework. The competent authority, the Comissao de Valores Mobiliarios (CVM), requires high standards of the entities it oversees and makes good use of the extensive data it receives from market participants on an ongoing basis. Fiduciary administrators play an important role as the main gatekeeper for investment funds and, despite the highly concentrated nature of the industry, there is evidence that they make a significant contribution to the safety and soundness of the sector as a whole.